The educational community and its knowledge and perceptions of native and invasive alien species - Sosa, Alejandro Joaquin; Jiménez, Nadia L.; Faltlhauser, Ana Claudia; Righetti, Tomás; Mc Kay, Fernando; Bruzzone, Octavio Augusto; Stiers, Iris; Fernández Souto, Adriana (Springer Nature, 2023)
Environmental education seeks to foster an appreciation for nature and the impact of humans on it while introducing citizens to scientific thinking. Biological invasions affect different aspects of life on earth and mandate urgent management actions. Education and public awareness are strongly recommended for successful prevention and management of invasive alien species (IAS). This work presents a study on knowledge and perception of the educational community of Argentina about native species and IAS. We designed an on-line semi-structured questionnaire to examine perception of the environment, recognition of native species and IAS and awareness about biological invasions. Educators recognised an important number of biotic components, mostly represented by trees, birds and mammals. Recognition of native species and IAS, and awareness of biological invasions were different between NST (Natural Science Teachers) and non-NST. Respondents had different performances when they were exposed to recognising native species though written names or photographs. Out of 532 respondents, 56% knew what biological invasions are, 21% answered “Maybe” and 23% had never heard about them. We need to foster capacity-building and encourage a two-way communication between educators and scientists, formally and informally, to engage the participation of the whole society in recognition, prevention and management of IAS.